Rehabilitasi Sosial Penyalahguna Narkoba Berbasis Keluarga dan Lingkungan di Desa Nagori Rabuhit Kecamatan Gunung Maligas Kabupaten Simalungun - Umi Khairiah; Jarnawi Jarnawi; Maswita Maswita; Anjani Sipahutar; Prinsi Rigitta; Andri Ramadhan (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Drug abuse is a social problem with widespread impacts on individuals, families, and communities. Repressive approaches are considered ineffective without balanced social rehabilitation based on family and community support. This Community Service (PkM) activity aims to implement a family- and community-based social rehabilitation model for drug abusers in Nagori Rabuhit Village, Gunung Maligas District, Simalungun Regency. The method used is a community-based participatory approach through outreach, counseling, discussions, and family mentoring, involving the village government, community leaders, and residents. The results of the activity indicate an increase in community understanding of the dangers of drugs, changes in more inclusive attitudes, and increased family capacity to provide emotional support, effective communication, and preventive supervision. Furthermore, the role of the social environment and village government in supporting the recovery process has been strengthened. This model has proven effective and sustainable in increasing community social resilience to drug problems.